Traditional uses of leguminosae among the Karen in Thailand - Natcha Sutjaritjai (2020)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Leguminosae (legumes) are one of the largest plant families. They are widely used for a variety of purposes by people around the world and include many important cultivated economic food crops. On local scales, legumes are commonly used by various ethnic groups. However, the data are incomplete and scattered, not least in Thailand. We found that species of legumes were important in Karen communities, so we decided to investigate in detail the traditional knowledge of legumes on a local scale among Karen people in northern Thailand. We interviewed six herbalists and eighty-four nonherbalist informants in three Karen villages in Chiang Mai province about their use of legumes, and about the local names for the species, using semistructured interviews. A total of 83 legumes species (in 45 genera) had 4443 use reports. Five of the 83 legume species had not been reported previously as used in Thailand. Most Karen use reports (43%) of legumes were for food, medicine (36%), and materials (8%), but in term of species more legumes (68 species) were used for medicine than for food (53 species). The legume genera with most used species were Crotalaria and Flemingia each with six species. The most important species are Tamarindus indica (CI = 3.38), Senegalia rugata (CI = 2.39), Glycine max (CI = 1.27) respectively.